Perencanaan Dan Biaya Reklamasi Lahan Bekas Tambang Area Tambang Batubara PT. Baturona Adimulya Desa Supat Barat Kecamatan Babat Supat Kabupaten Musi Banyuasin - Ebran Alkad; Tamrin Kasim; Yunasril Yunasril (Departemen Teknik Pertambangan FT UNP, 2018)
PT. Baturona Adimulya is a coal mining company located in West Supat Village, Babat Supat District, Musi Banyuasin Regency. PT. Baturona Adimulya has a Mining Mine with an area of ± 3,476 ha that has not been functioned. Current land conditions have elevation of 11 meters with slope ± 12% so that on the slope of the land, when the summer causes dust and rainy season cause erosion. The company plans to reclaim the former mine land. However, in the Mining Closure Plan document, it is mentioned that on this land the new planting plan takes into account the planting of pioneer plants (budding plant) ie sengon, while for planting of nucleus reclamation plants has not been determined between oil palm or rubber. Therefore, in the reclamation effort on ex-mining land, it is necessary to make good planning with planting of plants in accordance with the characteristics of the land. The technical planning of reclamation activities starts from knowing the characteristics of the soil, the arrangement of the land by leveling the condition of the embankment, then repairing the slope by making terracing, cover crop covering. Furthermore, the revegetation process starts from pengajiran, excavation planting hole, planting, and maintenance (2 years after the seed planting). Based on the results of laboratory testing, the characteristics of ex-mining land are suitable for planting rubber or oil palm plantations. Based on the calculation in the reclamation planning of ex-mining land by revegetation, the total cost is Rp. 507.372.156.00 for oil palm with sengon laut, and Rp. 505.052.919,00 for rubber with marine sengon.Keywords: ex-Mining Land, Reclamation Plan, Revegetation, Cost, Mining Closer